PENERAPAN GIMKIT UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA JERMAN SISWA KELAS XI SMA NEGERI 12 MAKASSAR - Akbar Aburaera, Hikmal Akbar; Dalle, Ambo; Mantasiah R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is a Classroom Action Research (CAR) aimed at examining the planning, implementation, and outcomes of using Gimkit as a learning medium. The subjects of this research were a teacher and 35 students from class XI.6. The study was conducted during the odd semester of the 2025/2026 academic year across two cycles, each consisting of four stages: planning, acting, observing, and reflecting. Two types of data were collected: quantitative data from students' vocabulary mastery test results at the end of each cycle, and qualitative data gathered through observations of both the teacher and students during the sessions. Prior to the intervention, students' German language test scores were relatively low; only 22 out of 35 students (63%) reached the Minimum Mastery Criterion (KKM) of 75. Based on the data analysis, the average student score at the end of Cycle I following the implementation of Gimkit was 69, representing a 3% increase from the initial baseline of 66. By the end of Cycle II, there was a further 16% increase, with the average score reaching 80. These results demonstrate that the application of Gimkit is effective in improving the German vocabulary mastery of students at SMA Negeri 12 Makassar.